Considerations about the fruit–growing and fruit farming in the Alto Val-le de Río Negro - Urraza, Maria Soledad (Universidad Nacional del Litoral, 2020)
The extension work with fruit farmers in the Alto Valle region is the one that calls for the reflection–action from different angles. This work starts from the necessary intervention for rural development centered on the most vulnerable links in the fruit production chain and goes through the current debates around fruit growing and the existence of family fruit farming. How is the fruit activity organized economically? How are the various economic agents inserted in the market? How heterogeneous is the sector of producers? Is there family fruit farming? What are the necessary conditions for the fruit farmers to organize themselves? With these questions, different opinions expressed in documents and current scientific works are analyzed and debated, contributing some reflections to move towards the design of public policies.